Phyllosphere microbiome-physicochemical dynamics shape nitrogen resorption efficiency divergence during leaf senescence in subtropical forests of southern China - Bing Xue; Guoping Tang; Zhongkai Ren; Linwei Zeng; Xiaobin Li; Yuqi Li; Nan Jiang (Forest Ecology and Management, 2026)

Carbon balance in an agriculture-disturbed forested headwater stream in South China: Variations and environmental controls - Houbing Chen; Yangbo Yu; Xupeng Fang; Nan Jiang; Bing Xue; Yuqi Li; Guoping Tang (Journal of Environmental Management, 2026)

Analysis and rapid prediction of underwater vehicle hydrodynamic loads during water-exit integrating CFD with GA-LSTM - Shutian Li; Guoping Wang; Bin He; Genyang Wu; Yibing Hou; Yu Feng; Jinxin Tang (Ocean Engineering, 2025)

Distinguished behaviors between stream CO2 and CH4 concentrations and the potential causes in a headwater catchment of southern China - Nan Jiang; Guoping Tang; Wenya Zhang; Houbing Chen; Xupeng Fang; Zhongkai Ren; Xixi Lu (Journal of Hydrology, 2025)

Heterologous expression of nodulation signaling pathway genes enhances grain yield in rice - Zheng Li; Hao Li; Guoping Tang; Jiashan Wu; Zhongming Zhang; Renliang Huang; Yangrong Cao (Plant Molecular Biology, 2025)

Urban trash bins as reservoirs of multidrug-resistant Enterococcus with shared resistance genes across clinical and environmental niches - Jie Li; Xiaorui Mao; Yu Song; Xiaohe Hu; Guoping Zhao; Biao Tang (Journal of Hazardous Materials, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

A knowledge-guided LSTM reservoir outflow model and its application to streamflow simulation in reservoir-regulated basins - Runting Chen; Dagang Wang; Yiwen Mei; Yongen Lin; Zequn Lin; Zhi Zhang; Shengjie Zhuang; Jinxin Zhu; Jonghun Kam; Yiping Wu; Guoping Tang (Journal of Hydrology, 2025)

Advancements in function recognition of staphyloxanthin and targeted inhibitor development - Jiang Chang; Min Yue; Guoping Zhao; Biao Tang; Chunlei Shi (Current Opinion in Food Science, 2025)

The defect engineering design of COCN/L-CdS/Ni2P for promoting hydrogen energy generation from seawater coupling with photoreforming of plastics - Zhe Yin; Ziwen Wang; Jun Wang; Binglin Tang; Guoping Yu; Qiuyu Wang; Huanyu Chen; Kangzheng Li; Zhichao Zhang; Qingcheng Luo; Fuqin Zhang; Bo Lv (Fuel, 2025)

Non-noble CeO2/CdS/NiS heterojunction for photoredox-catalyzed plastic waste selective synthesis and hydrogen production from natural seawater - Ziwen Wang; Qiuyu Wang; Zhe Yin; Man Zhang; Guoping Yu; Qingcheng Luo; Huanyu Chen; Binglin Tang; Kangzheng Li; Zhichao Zhang; Bo Lv (Fuel, 2025)

High instantaneous response quartz crystal microbalance humidity sensor for respiratory droplet detection - Jiaqi Lu; Xiangdong Chen; Xing Ding; Zhuolin Jia; Mengxi Zhang; Xiang Yu; Kun Tang; Fang Liu; Hui Li; Guoping Li (Chemical Engineering Journal, 2025)

Mycorrhizal dominance influences tree species richness and richness–biomass relationship in China's forests - Suhui Ma; Guoping Chen; Qiong Cai; Chengjun Ji; Biao Zhu; Zhiyao Tang; Shuijin Hu; Jingyun Fang (Ecology, 2025)
Mycorrhizal associations drive plant community diversity and ecosystem functions. Arbuscular mycorrhiza (AM) and ectomycorrhiza (EcM) are two widespread mycorrhizal types and are thought to differentially affect plant diversity and productivity by nutrient acquisition and plant–soil feedback. However, it remains unclear how the mixture of two mycorrhizal types influences tree diversity, forest biomass, and their relationship at large spatial scales. Here, we explored these issues using data from 1247 plots (600 m 2 for each) across China's natural forests located mostly in temperate and subtropical regions. Both AM‐dominated and EcM‐dominated forests show relatively lower tree species richness and stand biomass, whereas forests with the mixture of mycorrhizal strategies sustain more tree species and higher biomass. Interestingly, the positive effect of tree diversity on biomass is stronger in forests with low (≤50%) than high AM tree proportion (>50%), reflecting a shift from the complementarity effect to functional redundancy with increasing AM trees. Our findings suggest that mycorrhizal dominance influences tree diversity and richness–biomass relationship in forest ecosystems.

Molecular insights and functional analysis of isocitrate dehydrogenase in two gram-negative pathogenic bacteria - Wei Xiong; Rui Su; Xueyang Han; Mengxiao Zhu; Hongyiru Tang; Shiping Huang; Peng Wang; Guoping Zhu (World Journal of Microbiology and Biotechnology, 2024)

The sources and selectivity characteristics of organic carbon transported by debris flow events in a mountainous catchment, Southwest China - Zhengang Wang; Yizhe Zhang; Aimin Chen; Nufang Fang; Jianlin Zhao; Guoping Tang (Journal of Soils and Sediments, 2024)

Co-composting of dewatered sludge and wheat straw with newly isolated Xenophilus azovorans: Carbon dynamics, humification, and driving pathways - Xuan Wu; Runyu Gao; Xiaorui Tian; Jiawei Hou; Yang Wang; Quan Wang; Daniel Kuok Ho Tang; Yiqing Yao; Xiu Zhang; Bowen Wang; Guoping Yang; Hua Li; et al. (Journal of Environmental Management, 2024)

Integrated Metagenomics and 15N Isotope Tracing Reveal the Mechanisms Through which the Nitrogen-Planting Density Interaction Impacts Rice Root Nitrogen Uptake Efficiency - Changhui Sun; Yanyao Lu; Guoping Tang; Runnan Wang; Han Wu; Jiao Zhang; Shuo Cai; Jinyan Zhu; Qiangqiang Xiong (Journal of Soil Science and Plant Nutrition, 2024)

Grapefruit essential oil combined with UV-C treatment: A technology to improve the microbial safety of fresh produce - Ningbo Liao; Xinyun Chen; Mengxuan Tang; Peng Tian; Chengwei Liu; Lu Ruan; Hong Pan; Mei Shu; Chan Zhong; Guoping Wu (Innovative Food Science & Emerging Technologies, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Insight into the humification and carbon balance of biogas residual biochar amended co-composting of hog slurry and wheat straw - Yunpeng Liu; Junting Pan; Jingwen Wang; Xu Yang; Wanqiang Zhang; Kuok Ho Daniel Tang; Hailong Wang; Xiu Zhang; Runyu Gao; Guoping Yang; Zengqiang Zhang; Ronghua Li (Environmental Science and Pollution Research, 2024)

Unique ternary Pd/NH2-MIL-125/CdIn2S4 composite expands the absorption range of visible light and improves H2 evolution efficiency - Man Zhang; Kangzheng Li; Zhe Yin; Zhichao Zhang; Qingcheng Luo; Binglin Tang; Guoping Yu; Tianding Hu; Shaoyun Shan (Journal of Environmental Chemical Engineering, 2024)

Biotic and abiotic effects of manganese salt and apple branch biochar co-application on humification in the co-composting of hog manure and sawdust - Xuan Wu; Xinyu Zhao; Weilong Wu; Jiawei Hou; Wanqiang Zhang; Daniel Kuok Ho Tang; Xiu Zhang; Guoping Yang; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Chemical Engineering Journal, 2024)

Simultaneous decontamination of phosphorus and bisphenol A from livestock wastewater with boehmite-modified carbon composite - Yaru Peng; Xiu Zhang; Yuan Luo; Azeem Muhammad; Guoping Yang; Kuok Ho Daniel Tang; Zengqiang Zhang; Yuan Xu; Menghao Li; Jintong Cui; Ronghua Li (Bioresource Technology, 2024)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

A global analysis on the relationship between water retention time and dissolved carbon across inland waters - Nan Jiang; Guoping Tang; Tao Chen; Xiangyu Niu; Yangbo Yu; Yi Li (Aquatic Sciences, 2023)

Snow depth alteration and its relation with climate variability in China - Muattar Saydi; Guoping Tang; Jianli Ding; Zhengang Wang (International Journal of Climatology, 2023)
Various climatic factors and their interactions affect China's snow depth alterations. However, a measure of the relative importance of climatic factors regarding the variance in snow depth is lacking. Here, we use a heretofore largest dataset, quality‐controlled daily observations from 1,665 meteorological stations, and statistical analyses to identify proxy drivers and their contributions regarding regional variability and trends in China's snow depth and snow depth‐climate relationships from 1951 to 2019. Results show that seasonal snow depth alterations are substantial in China and caused by various climatic drivers. In winter, observed positive trends in the northwest and northeast of China mainly respond to augmentation in solid precipitation and snow accumulation in fall. For the Tibetan Plateau, the negative snow depth anomaly seems to respond to the rising air temperature below the freezing point along with some secular changes in solid precipitation and shallower fall snowpacks. All these trends in winter snow depth over the northwest, northeast, and Tibetan Plateau of China account approximately for 30% of the total interannual variance in spring snow depth in these regions. In the milder central north and south of China, snow accumulation is not evident. Besides solid precipitation and rising air temperature below the freezing point, atmospheric humidity is also notable for its effect on the interannual variance in winter snow depth in these regions. In spring and fall, however, the negative effect of warming climate on snow depth becomes remarkably more important. It seems that about 13–33% (12–50%) of the total interannual variance in the widespread decrease (insignificant perturbation), except for some weak increases in the northeast region (decreases in the Tibetan Plateau), of China's spring (fall) snow depth are caused by the rising air temperature below the freezing point.

Use of bentonite-coated activated carbon for improving the sensitivity of RT-qPCR detection of norovirus from vegetables and fruits: The ISO 15216-1:2017 standard method extension - Mengxuan Tang; Ningbo Liao; Peng Tian; Kaisheng Shen; Chengwei Liu; Lu Ruan; Guoping Wu (Food Microbiology, 2023)

SlERF.J2 reduces chlorophyll accumulation and inhibits chloroplast biogenesis and development in tomato leaves - Yanan Chen; Xi Cai; Boyan Tang; Qiaoli Xie; Guoping Chen; Xuqing Chen; Zongli Hu (Plant Science, 2023)

Soluble extracellular polymeric substance (SEPS) of histo-blood group antigen (HBGA) expressing bacterium Sphingobacterium sp. SC015 influences the survival and persistence of norovirus on lettuce - Ningbo Liao; Mengxuan Tang; Lili Chen; Peng Tian; Dapeng Wang; Dongqing Cheng; Guoping Wu (Food Microbiology, 2023)

The AP2/ERF transcription factor SlERF.J2 functions in hypocotyl elongation and plant height in tomato - Yanan Chen; Hong Yang; Boyan Tang; Fenfen Li; Qiaoli Xie; Guoping Chen; Zongli Hu (Plant Cell Reports, 2022)

The AP2/ERF transcription factor SlERF.F5 functions in leaf senescence in tomato - Yanan Chen; Panpan Feng; Boyan Tang; Zongli Hu; Qiaoli Xie; Shuang Zhou; Guoping Chen (Plant Cell Reports, 2022)

The regular pattern and underlying mechanisms of seawater intrusion in the Modaomen channel in the Pearl River Estuary of China - Muzhen Yang; Guoping Tang; Tao Jiang; Tao Chen; Xiaohua Chen (Environmental Science and Pollution Research, 2021)

Inconsistent responses of soil microbial community structure and enzyme activity to nitrogen and phosphorus additions in two tropical forests - Suhui Ma; Guoping Chen; Wenguang Tang; Aijun Xing; Xiao Chen; Wen Xiao; Luhong Zhou; Jiangling Zhu; Yide Li; Biao Zhu; Jingyun Fang (Plant and Soil, 2021)

Cardiac-specific LRP6 knockout induces lipid accumulation through Drp1/CPT1b pathway in adult mice - Ying Wang; Chao Yin; Zhidan Chen; Yang Li; Yan Zou; Xiang Wang; Yanpeng An; Feizhen Wu; Guoping Zhang; Chunjie Yang; Huiru Tang; Yunzeng Zou; et al. (Cell and Tissue Research, 2020)

SlHDA5, a Tomato Histone Deacetylase Gene, Is Involved in Responding to Salt, Drought, and ABA - Xiaohui Yu; Qiong Gao; Guoping Chen; Jun-E Guo; Xuhu Guo; Boyan Tang; Zongli Hu (Plant Molecular Biology Reporter, 2018)

Soil aggregate characteristics and stability of soil carbon stocks in a Pinus tabulaeformis plantation - Guoping Chen; Zhangying Gao; Lihong Zu; Lili Tang; Tong Yang; Xiaomei Feng; Tiejian Zhao; Fuchen Shi (New Forests, 2017)

Quantifying the changing properties of climate extremes in Guangdong Province using individual and integrated climate indices - Yanhu He; Kairong Lin; Guoping Tang; Xiaohong Chen; Shenglian Guo; Faliang Gui (International Journal of Climatology, 2017)
The temporal and spatial trends of four climate extreme indices for Guangdong Province of China were calculated based on observed daily precipitation, daily maximum, and daily minimum temperatures at 24 weather stations as well as the frequency of typhoon events during the period of 1957–2013. An integrated extreme climatic index ( IECI ) was derived from four individual climate extreme indices (high temperature days ( H td ), low temperature days ( L td ), intensive precipitation days ( I pd ) and number of typhoon events ( TT )), considering their weights using an information theory model. A simple linear regression model was utilized to analyze the spatiotemporal trends of the climate extremes. The correlation analysis between the above extreme climatic indices and the socioeconomic losses [affected area of crops ( AAC ), direct losses of the economy ( DLE ), and affected population ( AP )] was calculated. The results indicate that H td increased while L td decreased significantly at the 5% significance level. By contrast, there were no significant long‐term changes in I pd and TT . The rate of change of IECI was 0.006 per decade and no long‐term trend was detected in IECI . Spatially, a positive trend was observed in the Yuexi River Basin ( YXRB ) for I pd , while a negative trend was found in the East River Basin ( ERB ). L td followed an opposite spatial pattern to that of H td . Extreme temperature days occurred more frequently in the Pearl River Delta ( PRD ) than in other parts of Guangdong Province. Regions with positive IECI rates of change were mostly in the YXRB , the coastal area of the Yuedong River Basin ( YDRB ) and the northern and southern part of the ERB . The correlation coefficients between IECI and AAC , DLE , and AP are 0.375, 0.424 and 0.603, respectively. In general, IECI correlated more strongly with the loss indices caused by extreme climatic events than did the four individual extreme climatic indices.

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Optimization of well placement by combination of a modified particle swarm optimization algorithm and quality map method - Shuaiwei Ding; Hanqiao Jiang; Junjian Li; Guoping Tang (Computational Geosciences, 2014)

The potential transient dynamics of forests in New England under historical and projected future climate change - Guoping Tang; Brian Beckage; Benjamin Smith (Climatic Change, 2012)

Association between the IL7R T244I polymorphism and multiple sclerosis: a meta-analysis - Ruijie Zhang; Lian Duan; Yongshuai Jiang; Xuehong Zhang; Peng Sun; Jin Li; Mingming Zhang; Guoping Tang; Xing Wang; Xia Li (Molecular Biology Reports, 2011)

Effect of ac68 Knockout and lef3 Leading Sequence Disruption on Viral Propagation - Guohui Li; Huiqing Chen; Qi Tang; Guoping Huang; Riqiang Deng; Jinwen Wang; Xunzhang Wang (Current Microbiology, 2011)

A new metric for evaluating the correspondence of spatial patterns in vegetation models - Guoping Tang (Global Ecology and Biogeography, 2008)
Aim To present a new metric, the ‘opposite and identity’ (OI) index, for evaluating the correspondence between two sets of simulated time‐series dynamics of an ecological variable. Innovation The OI index is introduced and its mathematical expression is defined using vectors to denote simulated variations of an ecological variable on the basis of the vector addition rule. The value of the OI index varies from 0 to 1 with a value 0 (or 1) indicating that compared simulations are opposite (or identical). An OI index with a value near 0.5 suggests that the difference in the amplitudes of variations between compared simulations is large. The OI index can be calculated in a grid cell, for a given biome and for time‐series simulations. The OI indices calculated in each grid cell can be used to map the spatial agreement between compared simulations, allowing researchers to pinpoint the extent of agreement or disagreement between two simulations. The OI indices calculated for time‐series simulations allow researchers to identify the time at which one simulation differs from another. A case study demonstrates the application and reliability of the OI index for comparing two simulated time‐series dynamics of terrestrial net primary productivity in Asia from 1982 to 2000. In the case study, the OI index performs better than the correlation coefficient at accurately quantifying the agreement between two simulated time‐series dynamics of terrestrial net primary productivity in Asia. Main conclusions The OI index provides researchers with a useful tool and multiple flexible ways to compare two simulation results or to evaluate simulation results against observed spatiotemporal data. The OI index can, in some cases, quantify the agreement between compared spatiotemporal data more accurately than the correlation coefficient because of its insensitivity to influential data and outliers and the autocorrelation of simulated spatiotemporal data.

A new metric for evaluating the correspondence of spatial patterns in vegetation models - Guoping Tang (Global Ecology and Biogeography, 2008)